If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = k + -12k + 35 Reorder the terms: 0 = 35 + k + -12k Combine like terms: k + -12k = -11k 0 = 35 + -11k Solving 0 = 35 + -11k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '11k' to each side of the equation. 0 + 11k = 35 + -11k + 11k Remove the zero: 11k = 35 + -11k + 11k Combine like terms: -11k + 11k = 0 11k = 35 + 0 11k = 35 Divide each side by '11'. k = 3.181818182 Simplifying k = 3.181818182
| 7x-14=7x+14 | | n+0.15=1.15 | | 8(t-4)+4t=6(2t+2)-10 | | -12t=-60 | | 4(6x-6)=6(3x+1) | | 1.25=0.5s | | (P-3)(p-6)=0 | | n/0.3=9.9 | | D-(20)=2.5 | | r-8.5=2.1 | | -87-2w=-v+21 | | 7x+9=2x-14 | | -2(4s-3)-6=-3(8s+5)-5 | | w/-8=21 | | 2.4x+11.8=7.2-26.4 | | (6k+5)(5k-1)=0 | | Y=8/x-1 | | 1+4x+3x= | | Y=3y-3z | | c/-3=8 | | 9x+6x+7=16x-2x-8 | | x^2=-3x+2 | | 4x^2+15x-2=0 | | (2.4-2v)/3=9 | | (3x-5.7)-6=4.1 | | 3(x-2)=5(x-4) | | (3x-5.7)/6=4.1 | | (y+x)(y-x)=2x | | (8-n)-7=4/3 | | 9w+17=6w+32 | | (8-n)/7=4/3 | | Y+x= |